SOCS1 Regulates CCR7 expression and Migration of CD4(+) T Cells into peripheral Tissues - Yu, Cheng-Rong (2008)
Suppressors of cytokine signaling (SOCS) proteins control many aspects of lymphocyte function through regulation of STAT pathways. SOCS1-deficient mice develop severe skin and eye diseases that result from massive infiltration of inflammatory cells into these tissues. In this study, we have used SOCS1-, STAT1- or STAT6-deficient mice, as well as, T-cells with stable over-expression or deletion of SOCS1, to examine whether SOCS1 is involved in regulating lymphocyte trafficking to peripheral tissues. We show that SOCS1-deficient mice have increased numbers of T-cells with characteristic of effector memory cells and expression of CCR7, a protein that promotes retention of T-cells in lymphoid tissues, is markedly reduced in these cells. The decrease in CCR7 expression correlates with hyper-activation of STAT6, suggesting that aberrant recruitment of T-cells into SOCS1-deficient mouse skin or eye results from abrogation of negative-feedback regulation of STAT6 activation and CCR7 expression. Consistent with in vivo regulation of CCR7 expression and lymphocyte migration by SOCS1, forced over-expression of SOCS1 in T-cells upregulates CCR7 expression and enhances chemotaxis towards CCL19 or CCL21. CCR6 and CXCR3 are also upregulated on SOCS1-deficient T-cells and in situ analysis of the cornea or retina further reveal that these cells may mediate the chronic skin and eye inflammation through recruitment of T(H)1 and T(H)17 cells into these tissues. Collectively, these results suggest that SOCS1 regulates steady-state levels of chemokine receptors through its inhibitory effects on STAT pathways and this may underscore its role in regulating recruitment and retention of effector cells into non-lymphoid tissues.